Development and usability testing of a multifaceted intervention to reduce low-value injury care - Mélanie Bérubé; Alexandra Lapierre; Michael Sykes; Jeremy Grimshaw; Alexis F. Turgeon; François Lauzier; Monica Taljaard; Henry Thomas Stelfox; Holly Witteman; Simon Berthelot; Éric Mercier; Catherine Gonthier; et al. (BMC Health Services Research)
Abstract Background Multifaceted interventions that address barriers and facilitators have been shown to be most effective for increasing the adoption of high-value care, but there is a knowledge gap on this type of intervention for the de-implementation of low-value care. Trauma is a high-risk setting for low-value care, such as unnecessary diagnostic imaging and the use of specialized resources. The aim of our study was to develop and assess the usability of a multifaceted intervention to reduce low-value injury care. Methods We used the Consolidated Framework for Implementation Research and the Expert Recommendations for Implementing Change tool as theoretical foundations to identify barriers and facilitators, and strategies for the reduction of low-value practices. We designed an initial prototype of the intervention using the items of the Template for Intervention Description and Replication. The prototype’s usability was iteratively tested through four focus groups and four think-aloud sessions with trauma decision-makers (n = 18) from seven Level I to Level III trauma centers. We conducted an inductive analysis of the audio-recorded sessions to identify usability issues and other barriers and facilitators to refine the intervention. Results We identified barriers and facilitators related to individual characteristics, including knowledge and beliefs about low-value practices and the de-implementation process, such as the complexity of changing practices and difficulty accessing performance feedback. Accordingly, the following intervention strategies were selected: involving governing structures and leaders, distributing audit & feedback reports on performance, and providing educational materials, de-implementation support tools and educational/facilitation visits. A total of 61 issues were identified during the usability testing, of which eight were critical, 33 were moderately important, and 18 were minor. These issues led to numerous improvements, including the addition of information on the drivers and benefits of reducing low-value practices, changes in the definition of these practices, the addition of proposed strategies to facilitate de-implementation, and the tailoring of educational/facilitation visits. Conclusions We designed and refined a multifaceted intervention to reduce low-value injury care using a process that increases the likelihood of its acceptability and sustainability. The next step will be to evaluate the effectiveness of implementing this intervention using a pragmatic cluster randomized controlled trial. Trial registration This protocol has been registered on ClinicalTrials.gov (February 24th 2023, #NCT05744154, https://clinicaltrials.gov/ct2/show/NCT05744154 ).